Szwed i Polak czytają „Underdoga”. Kulturowe uwarunkowania recepcji dzieła literackiego - Żmuda-Trzebiatowska, Magdalena (Studia Europaea Gnesnensia, 2016)
In the article, the author considers cultural factors which affect the reading of literary work by Swedish and Polish audiences. The piece in question is Underdog by Torbjörn Flygt (2001, translated into Polish by Elżbieta Jasińska-Brunnberg, 2006). Analyzing the setting of the novel in historical narrative about the Swedish welfare state, the authors poses questions regarding universal or hermetic nature of Flygt’s novel.